Commercial banks lending and economic growth in Malaysia: An Empirical Study / Tang Tuck Cheong - Tang, T.C. (1999)
The objective of the study is to investigate, and explore the impact of commercial banks lending on economic growth in Malaysia with annual data for the period of 1960-98. The theoretical underpinning of the role of commercial banks lending to economic growth is based on combination of quantity theory of money and aggregate production function. The study shows an increasing of importance of commercial banks to economic growth. Obviously, commercial banks in Malaysia provided about 69 per cent to 72 per cent of total loan in banking system. The study shows an increasing rule of commercial banks lending in economic growth, GNP(Gross National Product), from RM0.073million in 1959 to RM1.14million in 1998 to generate a million of GNP in economic. The variables of Real Gross Domestic Product (RGDP), and commercial banks lending (LAc) are employed in the regression analysis. By using linear regression model (OLS), the finding reveals a short run (current year) positive influence of commercial banks lending to economic growth, but negative impact in long run (lagged explanatory variables). The findings also significantly explore the validity of theory in this study, Y=f(LAc). In addition, the commercial banks lending is found to be statistically significant variable to predict the future economic behavior.